Pengaruh Keamanan, Kemudahan Penggunaan dan Biaya Administrasi terhadap Keputusan Penggunaan Mobile Banking BSI dalam Transaksi E-Commerce (Studi pada Mahasiswa FEBI UIN Sulthan Thaha Saifuddin Jambi) - Meidina, Mutiara Alda; Anita, Efni; Subhan, Muhammad (Lembaga Yasin AlSys, 2024)
Security is an important factor because it affects a person's trust in using the service. Perceived ease of use is defined as the level of confidence that using the system does not require much effort. administrative costs are fees charged for an activity or can be called service fees. This study aims to determine the effect of security, ease of use and administrative costs on the decision of BSI Mobile Banking users in E-Commerce transactions. The population used in this study were students of the Faculty of Economics and Islamic Business at UIN Sulthan Thaha Saifuddin Jambi. The research method used is quantitative with the number of samples used as many as 95 students. The data analysis method used is power collection, data presentation, and sampling. This study uses the SmartPLS 4.1.0.0 statistical program to calculate and analyze data. The results of this study indicate that Security has a positive and significant effect on decisions to use BSI mobile banking in e-commerce transactions. Ease of use has a positive and significant effect on the decision to use BSI mobile banking in e-commerce transactions. Administration costs have a positive and significant effect on the decision to use BSI mobile banking in e-commerce transactions.